Bercerita di Depan Kelas untuk Meningkatkan Kemampuan Bahasa Anak Usia 5-6 tahun - Siti Asiyah (Jurnal Kualita Pendidikan, 2021)
Language advancements that occur in childhood, provide a foundation for further child development in elementary school To use language effectively, you need to know how to combine words to form meaningful expressions. This research was carried out on the basis of improving the language skills of group children. B3 Kindergarten M NU Maryithob 0S Banyurip Alit, Pekalongan City, which is diverse and classified as old, has not lived up to expectations. Therefore, one of the solutions offered is to use the storytelling method in front of the class to provide a more enjoyable and meaningful learning experience. This research is a qualitative research, with data collection techniques sourced from observation, interviews, documentation, and data triangulation. The purpose of this study was to describe and analyze storytelling in front of the class to improve language skills in early childhood. The results of the study concluded that storytelling activities in front of the class can improve the language skills of students in the B3 group of TK M NU Masyithoh 05 Banyunp Alit. In addition, storytelling activities in front of the class are interrelated in improving children's language skills. Storytelling activities in front of the class can improve language skills in group B3 TKM NU Masyithoh 05 Banyurip Alit students. This can be seen from the results of increased abilities in the four aspects of the assessment, namely large vocabulary, fluency in pronunciation, word pronunciation, and simple sentence formation